2017
DOI: 10.1212/wnl.0000000000004411
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation drives anxiety and depression in relapsing-remitting multiple sclerosis

Abstract: Mood alterations are induced by intrathecal inflammation, even though not clinically apparent, and are able to predict inflammatory reactivations in RRMS. Inflammation is therefore a biological event, not less important than the traditional psychosocial factors, involved in mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 38 publications
4
78
0
Order By: Relevance
“…On another hand, the expression of the anti-inflammatory cytokine IL-15 was unaltered. As neuroinflammation was shown to accompany pathological anxiety (Salim, 2017;Rossi et al, 2017) and since an increase in the synthesis of brain pro-inflammatory cytokines in mice can promote anxiogenic-like (Chen et al, 2013) and aggressive behaviors , present data implicate the reported here over-production of pro-inflammatory cytokines in the anxiogenic effects of ultrasound stress. We also demonstrated that in the ultrasound-exposed mice, elevated scores of anxietylike behaviors were associated with the over-expression of GSK-3β, that governs the production of pro-inflammatory cytokines , affects oxidative stress ) and regulates hippocampal cellular plasticity .…”
Section: Immunohistochemical Analysis Of Expression Of Internalizedsupporting
confidence: 65%
“…On another hand, the expression of the anti-inflammatory cytokine IL-15 was unaltered. As neuroinflammation was shown to accompany pathological anxiety (Salim, 2017;Rossi et al, 2017) and since an increase in the synthesis of brain pro-inflammatory cytokines in mice can promote anxiogenic-like (Chen et al, 2013) and aggressive behaviors , present data implicate the reported here over-production of pro-inflammatory cytokines in the anxiogenic effects of ultrasound stress. We also demonstrated that in the ultrasound-exposed mice, elevated scores of anxietylike behaviors were associated with the over-expression of GSK-3β, that governs the production of pro-inflammatory cytokines , affects oxidative stress ) and regulates hippocampal cellular plasticity .…”
Section: Immunohistochemical Analysis Of Expression Of Internalizedsupporting
confidence: 65%
“…The association of neuroin ammation with depression has been widely acknowledged as increased circulatory cytokines level has been determined in patients with mood disorders [70][71][72][73]. Peripheral immune activation leads to the transportation of cytokines to the central nervous system (CNS), which stimulates glial cell activation and subsequently accelerates central cytokine production via a positive feedback mechanism [13,72].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity number showed a dose-dependent association with increased risk of newly positive depression-screen. Comorbidities have been associated with clinical outcomes in MS (Marrie and Horwitz, 2010), and while some are potentially due to common inflammatory antecedents (Rossi et al, 2017), others like depression could be attributable both to common pathophysiological processes, and to MS symptoms and other comorbidities. Thus, it is not surprising that comorbidity number was positively associated with depression, even after adjustment for disability and fatigue.…”
Section: Discussionmentioning
confidence: 99%